2012
DOI: 10.1093/annonc/mdr589
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber and breast cancer risk: a systematic review and meta-analysis of prospective studies

Abstract: In this meta-analysis of prospective studies, there was an inverse association between dietary fiber intake and breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
3
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(153 citation statements)
references
References 56 publications
6
139
3
5
Order By: Relevance
“…482 Finally, reducing dietary fat intake, with a modest influence on body weight, may improve relapse-free survival rates of patients with breast cancer receiving conventional cancer treatment. 483 Fruits and vegetables contain large amounts of polyphenols.…”
Section: Healthy Eating Active Living and Emotional Resilience Goalsmentioning
confidence: 99%
“…482 Finally, reducing dietary fat intake, with a modest influence on body weight, may improve relapse-free survival rates of patients with breast cancer receiving conventional cancer treatment. 483 Fruits and vegetables contain large amounts of polyphenols.…”
Section: Healthy Eating Active Living and Emotional Resilience Goalsmentioning
confidence: 99%
“…In a recent meta-analysis of 16 prospective studies, a weak inverse association was found; for an increment of 10 g fiber per day, a 5% lower BC risk was seen. 24 Notably, most previous evidence on fiber intake and BC has been from studies in which women were enrolled during midlife or later; the effects of fiber during adolescence or early adulthood on BC incidence have been minimally studied. The atomic bombing of Hiroshima and Nagasaki and radiation treatment of Hodgkin's lymphoma indicate that breast tissue may be particularly susceptible to carcinogenic exposures during childhood and early adult life.…”
Section: What This Study Addsmentioning
confidence: 99%
“…A systematic review and meta-analysis of prospective studies in high-income countries showed a significant inverse association between dietary fiber intake and risk of BC 60 . The estimate suggested a decrease of 5% in the risk of BC per 10 g/day (95% CI: −9 to −2).…”
Section: Fibermentioning
confidence: 99%